2007
DOI: 10.1542/peds.2006-2549
|View full text |Cite|
|
Sign up to set email alerts
|

Do All Infants With Apparent Life-Threatening Events Need to Be Admitted?

Abstract: Our study suggests that >30-day-old infants who have experienced a single apparent life-threatening event may be discharged safely from the hospital, which would decrease admissions by 38%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 18 publications
1
43
1
10
Order By: Relevance
“…Observational data indicate that 12% to 14% of infants presenting with a diagnosis of ALTE had a subsequent event or condition that required hospitalization. 7,31 Thus, research has sought to identify risk factors that could be used to identify infants likely to benefit from hospitalization. A long-term follow-up study in infants hospitalized with an ALTE showed that no infants subsequently had SIDS but 11% were victims of child abuse and 4.9% had adverse neurologic outcomes (see 3.…”
Section: A Clinicians Need Not Admit Infants Presenting With a Lowementioning
confidence: 99%
See 2 more Smart Citations
“…Observational data indicate that 12% to 14% of infants presenting with a diagnosis of ALTE had a subsequent event or condition that required hospitalization. 7,31 Thus, research has sought to identify risk factors that could be used to identify infants likely to benefit from hospitalization. A long-term follow-up study in infants hospitalized with an ALTE showed that no infants subsequently had SIDS but 11% were victims of child abuse and 4.9% had adverse neurologic outcomes (see 3.…”
Section: A Clinicians Need Not Admit Infants Presenting With a Lowementioning
confidence: 99%
“…34 Preterm infants have been shown to have more serious events, although an ALTE does not further increase that risk compared with asymptomatic preterm infants without ALTE. 34 Claudius and Keens 31 performed an observational prospective study in 59 infants presenting with ALTE who had been born at >30 weeks' gestation and had no significant medical illness. They evaluated factors in the clinical history and physical examination that, according to the authors, would warrant hospital admission on the basis of adverse outcomes (including recurrent cardiorespiratory events, infection, child abuse, or any lifethreatening condition).…”
Section: A Clinicians Need Not Admit Infants Presenting With a Lowementioning
confidence: 99%
See 1 more Smart Citation
“…Essa dificuldade deve-se, sobretudo, à não especificidade do evento, que pode ocorrer tanto em lactentes saudáveis, sem significado patológico, quanto como a primeira manifestação de uma grande variedade de doenças com gravidade variada 3,5,[7][8][9][10][11][13][14][15][16][17][18][19] .…”
Section: Introductionunclassified
“…Tal situação indica, obrigatoriamente, internação, observação rigorosa, monitoramento e investigação diagnóstica 2,6,9,12,16,19,20 .…”
Section: Introductionunclassified